Effects of spatial management of a penaeid fishery on other target fish species in eastern Australia. (25th March 2022) - Taylor, Matthew D.; Hall, Karina C.; Johnson, Daniel D.
Abstract: Temporal and spatial closures are often used to manage harvest by trawl fisheries. Trawl closures implemented to benefit a particular species may also benefit other species, but these indirect effects are rarely quantified. Using the New South Wales (Australia) Ocean Trawl Fishery as a case study, the potential unintended effects of trawl closures designed to protect juvenile eastern king prawn were explored for other quota managed Sillaginidae within the fishery (stout whiting Sillago robusta and eastern school whiting Sillago flindersii ). Both species of whiting were more abundant within closed areas than adjacent areas, and spawning‐sized stout whiting were proportionally more abundant within closed areas. Thus, closures implemented to protect prawns also provided protection for exploited whiting species, including spawning‐sized individuals, enhancing their overall impact on the fishery. Spatial management of trawl fisheries elsewhere in the world may also similarly benefit other exploited species.